Essential dermatopathology - Edward, Sara. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2012)
"Dermatopathology is a very visual specialised field, so we felt it only right that we provide high quality images to help in the learning process - after all 'a picture is a thousand words'. This manual in no ways replaces the knowledge and information obtained by learning and being taught at the microscope or the viewing of many thousands of microscopic samples of skin specimens which one needs to see in order to become proficient at reading dermatopathology specimens. We hope this text book will serve as a helpful quick reference and an aid memoir to help facilitate the understanding of Dermatopathology"--Provided by publisher.